Effect of interface geometric parameters on the mechanical properties and damage evolution of layered cemented gangue backfill: Experiments and models. (26th September 2022) - Wang, Yiming; Wu, Jiangyu; Pu, Hai; Chen, Weiqiang; Yin, Qian; Yang, Shuo; Ma, Dan
Highlights: Mechanical properties of LCGB as a function of interface geometry parameters. Effects of interface geometric parameters on damage evolution of LCGB. Failure mode of LCGB is affected by interface geometric parameters. Dynamic crack evolution law of LCGB during loading. Abstract: Subsequent backfilling of widespread goaf generally necessitates multiple fillings to enrich the goaf, resulting in the layered structure of cemented gangue backfill. Therefore, it is of great significance to study the mechanical properties of layered cemented gangue backfill (LCGB) with different interface geometric parameters to ensure the stability of underground engineering. In this paper, the effects of interface roughness and interface angle on the mechanical properties and damage evolution of LCGB were comprehensively explored using uniaxial compression test, acoustic emission (AE) and digital image correlation (DIC). A numerical model of LCGB was built using simulation software (PFC2D) to demonstrate the dynamic crack evolution of LCGB during loading. The results demonstrate that LCGB's compressive strength and elastic modulus have positive linear and quadratic relationships with interface undulating angle and interface angle respectively, and that the rupture angle, which represents the worst mechanical properties of LCGB, is between 45° and 60°. Increasing the interface undulating angle can enhance the strain hardening characteristics of LCGB during the post-peak deformation stage and release more active AE signals. As the interface angle approaches the rupture angle, the peak stress of LCGB continues to deteriorate, and its AE signal appears more concentrated in the post-peak deformation stage. The surface principal strain of LCGB rises as the interface undulating angle increases, while it reduces first and then increases with the interface angle increases. The simulation process reveals that shear cracks mainly extend along the interface, whereas tension cracks propagation and coalescence the adjacent interface along the axial stress loading direction, and they converge to generate macroscopic defects that cause LCGB unstable failure.